Simultaneous Quantification of Limonin, Two Indolequinazoline Alkaloids, and Four Quinolone Alkaloids in Evodia rutaecarpa (Juss.) Benth by HPLC-DAD Method. (8th May 2013) - Zhang, Pei-ting; Pan, Bi-yan; Liao, Qiong-feng; Yao, Mei-cun; Xu, Xin-jun; Wan, Jin-zhi; Liu, Dan; Xie, Zhi-yong
Abstract : A simple and efficient HPLC-DAD (225 nm) method was developed and validated for the simultaneous determination of limonin and six key alkaloids (evodiamine, rutaecarpine, 1-methyl-2-undecyl-4(1H)-quinolone, evocarpine, 1-methy-2-[(6Z, 9Z)]-6, 9-pentadecadienyl-4-(1H)-quinolone, and dihydroevocarpine) in Evodia rutaecarpa (Juss.) Benth, which has been widely used as one of the Traditional Chinese Medicines. The chromatographic separation was carried out on a Hypersil BDS C18 column, and gradient elution was employed with a mobile phase containing acetonitrile and water. Contents of the analytes in 18 batches of samples were analyzed by ultrasonic extraction with ethanol and water mixture (80 : 20, v/v) followed by HPLC analysis. Separation of the seven analytes was achieved within 60 min with good linearity (r > 0.999 ). The RSD of both the intraday and interday precision was below 1.85%. The accuracy at different concentrations was within the range of 97.91 to 100.49%. Hierarchical clustering analysis was performed to differentiate and classify the samples based on the contents of the seven constituents. This study indicated that the quality control of E. rutaecarpa could be simplified to the measurement of four constituents, and that limonin, 1-methyl-2-undecyl-4(1H)-quinolone, and dihydroevocarpine should also be served as the chemical markers together with evodiamine for the quality control of Evodia rutaecarpa (Juss.) Benth.